Constraining relativistic beaming model for γ-ray emission properties of jetted AGNs - Onah Costecia I.; Iyida Evaristus U.; Eya Innocent O.; Odo Finbarr C. (Open Astronomy)
In this study, we investigate the hypothesis that γ-ray emissions from jetted active galactic nuclei (AGNs) are strongly beamed using the dominant relativistic beaming model of the samples of 532 blazars (281 flat-spectrum radio quasars [FSRQs] and 251 BL Lacertae objects [BL Lacs]) and 16 narrow line Seyfert 1 galaxies (NLSy1s). Our comparison of the distribution of the radio core-dominance (R) reveals that FSRQs exhibit the highest core dominance with a mean value of 1.32 ± 0.08, followed by BL Lacs at 1.21 ± 0.05, and NLSy1s at 0.93 ± 0.21. Our analysis indicates that over 80% (approximately 426) of our samples have log R > 0, with the values for FSRQs and BL Lacs extending by more than one magnitude. This suggests that γ-ray emissions in BL Lacs and FSRQs are significantly and relativistically boosted, while the effect is less pronounced in NLSy1s. Additionally, the data show that NLSy1s have the largest mean viewing angle compared to FSRQs and BL Lacs. This implies that at very small viewing angles, relativistic beaming and orientation effects are more significant in blazars than in NLSy1s. Further analysis reveals a moderate positive correlation (coefficient r ∼ 0.50) between the core-dominance parameter and both the γ-ray luminosity and redshift for the combined samples. These results are consistent with the relativistic beaming model and suggest that γ-ray emissions from blazars and NLSy1 galaxies are strongly beamed. This comprehensive analysis supports the notion that relativistic beaming plays a critical role in testing the hypothesis of γ-ray emissions of jetted AGNs. Thus, our findings contribute to a deeper understanding of the concept of relativistic beaming in different types of jetted AGNs, highlighting the importance of viewing angles and relativistic effects in interpreting γ-ray observations.